Increase Children's Creativity by Playing Musical Instruments and Dancing - Fajri, Al; Normayanti, Asiva Lela; Susilawati, Susilawati (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2024)
Children's creativity is an important aspect that needs to be improved in the process of education and learning. Early childhood is a critical period in the development of creativity. This article aims to explore the positive impact of the method of playing musical instruments and dancing on children's creative development. The purpose of this literature study is to understand the extent of existing knowledge, identify research gaps and summarize relevant findings from existing literature sources. This literature study helps researchers design conceptual frameworks, detailed theoretical frameworks and acquire a solid foundation for the research to be conducted. It can be concluded that this method can help improve imagination, fine and gross autoric physical abilities, social skills, cognitive.